Penerapan Model Problem Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis dalam Pembelajaran IPAS di SDN 9 Limboto - Puspita, Ita; Munirah, Munirah; Akolo, Ingka Rizkyani (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The aim of this study is to enhance students' critical thinking skills using the Problem Based Learning model in Natural and Social Sciences (IPAS) at SD Negeri 9 Limboto. Classroom Action Research is the method used in this study, whicth consistss of how ciycles, including planing, impllementation, observattion, andreflection. Thisis study was conducted during the 2024/2025 academic year, with 24 fifth-grade students as subjects. The research found that the use of the Problem Based Learning model can significantly stimulate students' critical thinking skills. In the first cycle, 58% of students met the Minimum Completion Criteria with an average score of 70.31%, while in the second cycle, 96% of students exceeded the KKM standard with an average score of 84.35%. This improvement demonstrates the effectiveness of the Problem Based Learning model in enhancing students' critical thinking skills to analyze, synthesize, and evaluate information, as well as fostering enthusiasm among students towards learning.